Wine Pairing for Traditional Indonesian Dishes: A Case Study of Rendang and Betutu Chicken - Lindayani Lindayani; Laksmi Hartajanie; Felix Yuwono Wiredjo; Dyah Wulandari (Soegijapranata Catholic University, 2026)
Indonesia is famous for its rich culinary heritage, which is characterized by complex spice blends. This uniqueness presents both challenges and opportunities for wine and food pairing. Wine is becoming increasingly popular among young Indonesian consumers, and interest in pairing it with traditional dishes is growing. However, comprehensive research on wine pairing with Indonesia cuisine remains limited. This study examines the sensory interactions between food characteristics and wine attributes through a literature review. The finding suggests that the ideal red wine for rendang should have moderate tannins and balanced acidity. In contrast, betutu chicken pairs better with white wine, particularly aromatic, off-dry varieties; the acidity and slight sweetness of the wine effectively balance the spiciness of the dish. These insights emphasize the necessity of adapting traditional wine pairing methods to align with the distinctive characteristics of Indonesian cuisine, leading to culturally relevant pairing approaches.